The efficiency of silicious nano nutrition on cotton productivity in arid regions - Khaitov, Botir; Abdualimov, Shukhrat; Allanov, Kholik; Khalikov, Bakhodir; Avliyakulov, Mirzoolim; Islamov, Sokhib; Norqulov, Usmonqul; Sheraliev, Khamidulla; Yuldasheva, Rano; Rajabov, Nurmamat; Murtazayeva, Gulnoza; Avliyoqulova, Musharraf; et al. (Frontiers in Sustainable Food Systems, 2024)
Since silicon (Si) was found to be effective in crop production recently, more information is needed about its characteristics, including how it functions as a nano fertilizer for crop performance. Therefore, this study aimed to evaluate the impact of the Si-containing nano fertilizer on cotton growth parameters and productivity in the arid region. The research conducted in open field conditions over the two consecutive growing seasons (2021 and 2022) revealed that the application of the Si-containing product significantly increased the biomass (10.6%), economic (19.4%), seed (14.3%), and lint yields (18.2%) of cotton as compared to the control group values. Likewise, the cotton biomass, economic, seed, and lint yields were increased by 11.8, 9.7, 9.5, and 9.1%, respectively, compared to the control variables after the Uzbiogumin application. Agronomic nitrogen-use efficiency (aNUE), physiological nitrogen-use efficiency (pNUE), internal nitrogen-use efficiency (iNUE), and apparent nitrogen recovery efficiency (aNRE) parameters were increased by 2.4-fold, 2.1-fold, 34.6 and 57.3%, respectively, with the application of Si nanonutrition. Although the cotton treated with nano Si produced a greater yield, while Uzbiogumin application resulted in more cotton biomass. Based on the results it can be concluded that the applied nano Si product can be widely used to increase crop productivity, especially in degraded lands under arid environments.